Children in The Circle of Criminal Practices In Ogan Komering Ilir Regency, South Sumatera - Sartika, Diana Dewi; Supraja, Muhammad (Komunitas, 2021)
This study aims to explore the practices of crimes committed by children in Bourdieu perspectives. Therefore, this study focuses on seeing how Habitus, Capital and Field surround the lives of child perpetrators of crimes (ABH/ Children in Conflict with the Law). This study was qualitatively conducted using a critical ethnographic approach. The results of the study showed that field as a medium for the fight of the capital owners is the one which is familiar with crime habitus. This condition also indirectly becomes the transmission media for the crime habitus on children. The capital owners involved in the circle of crimes by children, may include: owners of Solo Organ Orchestra (OT), drug dealers (thugs/bandits, weapon suppliers), internet cafe owners, as well as formal, informal figures, and adult leaders around the children. This study concludes that normatively children are guilty. However, children are actually also victims of a physical and social environment that does not support children to grow in a positive direction.